PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Adek Nilasari Harahap; Ishak Harahap (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2019)
The research aims are to determine the improvement of students' critical thinking skills in mathematics by using the STAD Cooperative learning model. The type of research is Classroom Action Research (CAR), which consists of 2 cycles. The subjects of this research are class VIII-4 of SMP Negeri 4 Padangsidimpuan, totalling 27 people. The object of this research is the Student Team Achievement Division (STAD) learning model to improve students' critical thinking skills. The results showed that the student learning tests by applying the STAD Type Cooperative learning model in the first cycle has obtained with a minimal category of 70.93% and in the second cycle increased to 86.04%. The increase from the period I to period II was 15.11%. With the achievement, the indicator has achieved by ≥ 80%. Then the results of the observations of student activities in the first cycle obtained levels of student activity of 71.97% "Enough" in the second cycle 85.24% with "Good" criteria. The increase that occurred period I to period II was 13.27%. Achievement indicator has accepted ≥ 80%. For the results of the observations the ability of teachers in the first cycle and second cycle obtained by the category of "Good". Keywords: Learning Outcomes, Critical Thinking Ability, STAD Type Cooperative Learning Model